Stab incision mitomycin C-assisted rapid trabeculectomy: A ‘SMART’ trabeculectomy alternative - Terzidou, Chryssa (Exp Ther Med, 2020)
The aim of the present study was to introduce a new modified trabeculectomy technique, stab incision mitomycin C (MMC)-assisted rapid trabeculectomy (SMART), which requires less surgical time and tissue manipulation. A total of 41 eyes with indication for trabeculectomy underwent glaucoma surgery with the SMART technique; superior subconjunctival injection of 0.005 mg MMC mixed with 0.1 ml lidocaine, followed by small, fornix base conjunctival opening. A stab incision was made to enter the anterior chamber 1.5 mm post-limbus using a 2.4 mm cataract knife. Double 0.75 mm punch and peripheral iridectomy were performed. A releasable suture was placed in the scleral opening, and matrix sutures to close conjunctiva. The preoperative mean intraocular pressure (IOP) was 23.8 mmHg, with a mean number of medications of 3.3. The mean follow-up duration was 27.6 months, with a range of 12-46 months. A year post-surgery, the mean IOP was 11 mmHg, with a mean number of medications of 0.7, corresponding to a reduction of 12.8 mmHg in IOP and 2.6 in the number of medications. During follow-up, additional 5-fluorouracil injections were administered when needed. In conclusion, SMART with wound modulation appears to be a safe and quick alternative to classic trabeculectomy. Few minor and no major complications were observed during the first 2.5 years of follow-up, with all eyes maintaining an IOP <15 mmHg.